The Duality of Shakuni: Trauma, Manipulation and Moral Conflict in the Mahabharata - Karki, Anushka; Paudel, Sushil (SCHOLARS: Journal of Arts & Humanities, 2025)
The Mahabharata is an epic that shapes the understanding of morality within the Hindu community. Foremost among its villainous characters is Shakuni who is portrayed as the personification of evil and the cause of the Kurukshetra war. This study examines the character of Shakuni and his experiences to understand the causes behind his supposed evilness and present his underexplored traits of goodness. Through content analysis of The Mahabharata by John D. Smith and other fictional and folk renditions of the epic, Shakuni’s duality has been examined and interpreted. The study analyzes themes of trauma, manipulation and moral conflict by using Caruth’s trauma theory, Jung’s theory of collective unconscious and archetypes, and Freudian psychoanalysis to uncover Shakuni’s maleficence as a consequence of circumstances rather than an inherent trait. Findings reveal that the traumatic experiences of losing loved ones and subjection to humiliation led to a change in Shakuni’s identity and unveiled the universal tendency to deceive or trick others to fulfil his revenge driven actions. It also evoked a conflict within his innate tendencies and ideal self, which resulted in the expression of his trauma in the form of vengeance. This study concludes Shakuni as a character with duality; an amalgamation of both positive and negative attributes, contrary to his popular depiction as a corrupt and vicious character, providing a basis for further exploration on the polarity of seemingly dishonorable characters.